The Impact of Palm Oil Plantation on the Community Well-Being in Langgikima District Konawe Utara Regency: Structural Equation Modeling Analysis Partial Least Square (PLS) Approach - Iskandar Zainuddin Rela; Weka Widayati; Ine Fausayana; Dian Agustina; Hartina Batoa; Tjandra Buana (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2023)
Enterprises in the oil palm plantation industry may be anticipated to influence community welfare since North Konawe Regency can contribute to regional development and community welfare due to its highly fertile plantation land. This study examines the impact of oil palm plantations on people's welfare in Langgikima Districts, North Konawe Regency. This research was carried out in February 2022, using a survey method with 150 respondents who felt a direct impact from the activities of oil palm plantation companies. The two critical factors examined are the activity of oil palm farms and community well-being. The data is processed using SEM (Structural Equation Modeling) analysis operated through the SMART PLS program. The study results show that the impact of oil palm plantations on the welfare of the people of North Konawe Regency has a significant and positive relationship, with the strength of the relationship being in the weak category. This means that the more economical, social, and environmental empowerment activities from the oil palm plantation business, the more it supports improving community well-being. The existence of oil palm plantations has had an impact on social well-being, economic well-being, and environmental well-being.